(untitled) (Minerva, 2019)
This paper argues that a distinction between the brief and the middle texts should be made within the so-called short Homeric Hymns. The conclusive section of the Homeric Hymns is examined from this point of view. Thus it is established that the formal features point to differences in the way of performance. The author proposes that the middle hymns were basically used as proems to other compositions, meanwhile it seems very plausible that the brief ones were employed as prayers.